A localist approach to the semantics and distribution of X-marking - Mizuno, Teruyuki (Proceedings of the Amsterdam Colloquium, 2024)
I propose an account that assigns a uniform semantics to each local occurrence of X-marking. The proposed account correctly captures the distribution of X-marking in conditionals and desire reports in English and Greek (and possibly many other languages).